Calliphoridae, Fanniidae, Muscidae e Sarcophagidae em um fragmento de Mata Atlântica na Ilha do Governador, Rio de Janeiro, RJ - Brasil - Leandro, Marcelo José Fonseca (2003)
Study of the diversity of the dipterans of the families Calliphoridae, Fanniidae, Muscidae and Sarcophagidae in a fragment of the "Mata Atlântica" rainforest located in the Ilha do Governador, Rio de Janeiro State, Brazil, during the period between July of 2001 and July of 2002. It was also analyzed the temporal variation occurrence of the most frequent species of the studied families on the fragment area and after they were related with the results obtained from the climatic variables. The collects were realized with traps based on FERREIRA (1979) e KHOURI (1991) with some modifications and utilizing baits of rotten fish. It was captured 3.604 specimens being the Calliphoridae the most abundant with 2.267 specimens (63% of the total captured), followed by the Fanniidae with 551 (15%), Muscidae with 437 (12%) and Sarcophagidae with 349 (10%). When considered the species diversity the Family Sarcophagidae obtained the best result with 22 species; followed by the Families Muscidae and Calliphoridae, each one with 8 and Fanniidae with 7. From the analysis realized it was seen that the number of captured individuals was higher when the temperature and humidity raised and this number was lower when the pluviosity raised. So the temperature and humidity had positive influence over the total number of captured individuals whilst the pluviosity had negative influence. The most frequent and most constant species was Chrysomya megacephala (Fabricius, 1794) which is exotic and was introduced for a little more than twenty years in the American Continent.